Assessing Magnetic Susceptibility Profiles of Topsoils under Different Occupations - N. Bouhsane; S. Bouhlassa (International Journal of Geophysics)
Magnetic susceptibility measurements at low and high frequencies (χlf, χhf) were carried out on topsoil samples from reforested, cultivated, and pasture lands from a catchment located at the north of Morocco. The aims of this study were to investigate the impact of land use or human activity on χlf of soil overlying the same substrate, to discriminate allochthonous material or pollution from autochthonous or inherited ones, and to assess the origin and contribution of superparamagnetic (SP) grains to the global magnetic susceptibility χlf. Measurements of χlf indicated significant enhancement, with values ranging from 12.4 to 252.82 × 10-8 m3 kg−1 with a mean value of 107.087 × 10-8 m3 kg−1 for the reforested lands. In the cultivated lands, χlf were from 8.4 to 88.65 × 10-8 m3 kg1 with a mean value of 42.69 × 10-8 m3 kg−1, while in the pasture lands, χlf was comprised between 14.34 × 10-8 m3 kg−1 and 133.35 × 10-8 m3 kg−1 with a mean value of 57.33 × 10-8 m3 kg−1. The magnetic enhancement indicates high concentration of ferrimagnetic minerals in the top soil. The magnetic susceptibility enhancement decreases as the human activity increases, while the underlying bedrock is almost the same: reforested land > pastures land > cultivated land. The analysis of the variations of χlf and frequency dependent susceptibilities (χfd and %χfd), along the profiles of soil, indicate a pedogenic origin of the topsoil magnetic susceptibility enhancement.